New Geophysical Data About the Pacific Margin (West Antarctica) Magnetic Anomaly Sources and Origin - Soloviev, V.D.; Bakhmutov, V.G.; Korchagin, I.N.; Yegorova, T.P. (Український антарктичний журнал, 2018)
During the seasonal work in the Ukrainian Antarctic expeditions (1997—2012), a significant amount of geological and geophysical studies were carried out. The main objective of the study is to obtain new data on the distribution of deep heterogeneities in the structures of the region. It’s allowed to construct the geophysical models and to discuss the existing ideas about the stages of formation and evolution tectonic structures of the West Antarctica near the Antarctic Peninsula (AP). New geophysical models of the Earth's crust were used to study the possible nature of the Pacific Coast magnetic anomaly (PMA) near the AP.